Oriented graphite layer formation in Ti/C and TiC/C multilayers deposited by high current pulsed cathodic arc - Persson, P.; Ryves, L.; Tucker, Mark; McKenzie, D.; Bilek, M. (American Institute of Physics, 2008)
Ti/C and TiC/C multilayers with periods ranging from 2 to 18 nm were grown by filtered highcurrent pulsed cathodic arc. The growth was monitored in situ by ellipsometry and cantilever stressmeasurements. The ellipsometry results reveal that the optical properties of the carbon vary as afunction of thickness. Correspondingly, the stress in each carbon layer as measured in situ exhibitstwo well defined values: initially the stress is low and then takes on a higher value for the remainderof the layer. Transmission electron microscopy shows that the initial growth of carbon on Ti or TiClayer is oriented with graphitic basal planes aligned parallel to the interface. After 2–4 nm of growth,the graphitic structure transforms to amorphous carbon. Electron energy loss spectroscopy showsthat the carbon layer simultaneously undergoes a transition from sp2 rich to sp3 rich material.